Endogenous parathyroid hormone–related protein compensates for the absence of parathyroid hormone in promoting bone accrual in vivo in a model of bone marrow ablation. (19th August 2013) - Zhu, Qi; Zhou, Xichao; Zhu, Min; Wang, Qian; Goltzman, David; Karaplis, Andrew; Miao, Dengshun
ABSTRACT To assess the effect of hypoparathyroidism on osteogenesis and bone turnover in vivo, bone marrow ablation (BMXs) were performed in tibias of 8‐week‐old wild‐type and parathyroid hormone–null (PTH−/−) mice and newly formed bone tissue was analyzed from 5 days to 3 weeks after BMX. At 1 week after BMX, trabecular bone volume, osteoblast numbers, alkaline phosphatase‐positive areas, type I collagen‐positive areas, PTH receptor–positive areas, calcium sensing receptor–positive areas, and expression of bone formation–related genes were all decreased significantly in the diaphyseal regions of bones of PTH−/− mice compared to wild‐type mice. In contrast, by 2 weeks after BMX, all parameters related to osteoblastic bone accrual were increased significantly in PTH−/− mice. At 5 days after BMX, active tartrate‐resistant acid phosphatase (TRAP)‐positive osteoclasts had appeared in wild‐type mice but were undetectable in PTH−/− mice, Both the ratio of mRNA levels of receptor activator of NF‐κB ligand (RANKL)/osteoprotegerin (OPG) and TRAP‐positive osteoclast surface were still reduced in PTH−/− mice at 1 week but were increased by 2 weeks after BMX. The expression levels of parathyroid hormone–related protein (PTHrP) at both mRNA and protein levels were upregulated significantly at 1 week and more dramatically at 2 weeks after BMX in PTH−/− mice. To determine whether the increased newly formed bones in PTH−/− mice at 2 weeks after BMX resulted from the compensatory action of PTHrP, PTH−/−PTHrP+/− mice were generated and newly formed bone tissue was compared in these mice with PTH−/− and wild‐type mice at 2 weeks after BMX. All parameters related to osteoblastic bone formation and osteoclastic bone resorption were reduced significantly in PTH−/−PTHrP+/− mice compared to PTH−/− mice. These results demonstrate that PTH deficiency itself impairs osteogenesis, osteoclastogenesis, and osteoclastic bone resorption, whereas subsequent upregulation of PTHrP in osteogenic cells compensates by increasing bone accrual. © 2013 American Society for Bone and Mineral Research